Molecular weight-based profiling of sperm proteins and their association with semen quality in Kokok Balenggek roosters - Jaswandi, Jaswandi; Gusdinal, Harif; Maulana, Tulus; Kaiin, Ekayanti Mulyawati; Rusfidra, Rusfidra; Ananda, Ananda (Journal of Advanced Veterinary and Animal Research, 2026)
Objective: The study characterized the sperm proteins of Kokok Balenggek roosters based on molecular weight patterns to investigate the relationship between sperm composition and semen quality. Materials and Methods: Semen from 15 Kokok Balenggek roosters was collected and tested for standard quality indicators, including volume, motility, viability, abnormalities, and plasma membrane integrity (PMI). The protein content was measured, and the sperm protein profile was established by applying SDS-PAGE on a 10% polyacrylamide gel. In the next phase, the statistical correlation between the indicators of semen quality and the total protein levels, as well as the protein fractions defined by the molecular weight, was determined. Results: Through the SDS-PAGE analysis, a total of 46 protein bands with molecular weights ranging from 8 to ≥ 245 kDa were identified in KBR semen. The average volume of fresh semen was 597.67 ± 325.20 µl, the motility was 80.78% ± 12.92%, the viability was 87.56% ± 5.33%, the abnormality was 10.60% ± 2.30%, and the PMI was 85.06% ± 5.37%. There was a forceful positive correlation between the number of protein bands and sperm motility (r = 0.91, p < 0.01). High molecular weight proteins (≥ 218–247 kDa) showed negative associations with motility and viability, while low molecular weight proteins (< 30–40 kDa) were linked to sperm quality parameters in a positive way. The previous studies propose that these molecular weight ranges may be indicative of BSP proteins ( 28–32 kDa), glycoproteins ( 40–42 kDa), HSP70/HSP90 ( 60–75 kDa), SPAG6 ( 72 kDa), and fibronectin or larger heat shock proteins ( 200–250 kDa), among others. Conclusion: The evaluation of KBR sperm proteins through their molecular weight profiles may yield initial clues to the potential semen quality markers, which is one of the main limitations of current research. J. Adv. Vet. Anim. Res., 12(4): 1430–1440, December 2025 http://doi.org/10.5455/javar.2025.l1003